Adolescents Lack Sufficient Maturity to Consent to Medical Research. Issue 3 (2017) - Cherry, Mark J.
Abstract : This study explores the ways in which adolescents, even so-called "mature minors", lack adequate development of the intellectual, affective, and emotional capacities necessary morally to consent to medical research on their own behalf. The psychological and neurophysiological data regarding brain maturation supports the conclusion that adolescents are qualitatively different types of agents than mature adults. They lack full adult maturity and personal agency. As a result, in addition to the usual requirements for IRB approval, one or both parents, or a legal guardian, should provide informed consent for minor children to participate in medical research.